The Safeguard of Audio Collections: A Computer Science Based Approach to Quality Control—The Case of the Sound Archive of the Arena di Verona. (14th December 2013) - Bressan, Federica; Rodà, Antonio; Canazza, Sergio; Fontana, Federico; Bertani, Roberta
Abstract : In the field of multimedia, very little attention is given to the activities involved in the preservation of audio documents. At the same time, more and more archives storing audio and video documents face the problem of obsolescing and degrading media, which could largely benefit from the instruments and the methodologies of research in multimedia. This paper presents the methodology and the results of the Italian project REVIVAL, aimed at the development of a hardware/software platform to support the active preservation of the audio collection of the Fondazione Arena di Verona, one of the finest in Europe for the operatic genre, with a special attention on protocols and tools for quality control. On the scientific side, the most significant objectives achieved by the project are (i) the setup of a working environment inside the archive, (ii) the knowledge transfer to the archival personnel, (iii) the realization of chemical analyses on magnetic tapes in collaboration with experts in the fields of materials science and chemistry, and (iv) the development of original open-source software tools. On the cultural side, the recovery, the safeguard, and the access to unique copies of unpublished live recordings of artists the calibre of Domingo and Pavarotti are of great musicological and economical value.